Some of Optical Properties to Titanum Dioxide thin Films at different Calcined Temperatures - Khadijh. S. Mohan (Journal of Global Pharma Technology, 2019)
The thin films of titanium dioxide were prepared by sol-gel technique and were deposited by using spin coating method. Some of the optical properties were diagnosed at different annealing temperatures.  Films prepared have been calcined at various temperatures degree for 1 hours or less for each film. The changes of optical properties with the effect of temperatures like optical absorption, optical transmittance and optical reflectivity have been diagnosed and characterized by ultra violet-visible spectrophotometer device. By the way the optical refractive index and optical energy gap were calculated from the relationship mathematical equations that will be mentioned in the results and discussion. It is worth noting that the curves were modified by using polynomial correction. Optical absorptions have been  increased with annealing temperatures, optical reflectivity and  optical refractive index with increasing of annealing temperature at the wavelengths confined between ~ 600nm to ~800nm, while the optical  transmittance showed an opposite results  of the optical  absorbance and  optical energy gaps decreasing with increasing of calcined temperatures.Keywords: Sol-gel, Calcined temperatures and optical transmittance.